Effects of gatekeeper trainings from the Austrian national suicide prevention program - Plöderl, Martin; Fartacek, Clemens; Kapitany, Thomas; Schrittwieser, Ulrike; Niederkrotenthaler, Thomas (Frontiers in Psychiatry, 2023)
Background: The development and implementation of gatekeeper trainings were first goals in the national suicide prevention strategy “suicide prevention Austria” (SUPRA). The current study aims to assess the short- and longer-term effects of the SUPRA gatekeeper trainings in comparison with established gatekeeper trainings. Methods: We evaluated 28 gatekeeper trainings including 427 participants by assessing improvement of knowledge (facts about suicide and suicide prevention), gatekeeper self-efficacy and attitudes, and gatekeeper behavior (e.g., asking depressed people about suicide). Assessments were immediately before and after the gatekeeper trainings, with an additional follow-up six months later. Effects were compared with benchmark effects of established gatekeeper trainings. Results: There were substantial improvements in knowledge, self-efficacy and attitudes immediately after the training, comparable or larger than known from evaluations of established gatekeeper trainings. Most of these changes were upheld in the follow-up assessment, with effects comparable to other gatekeeper trainings. There was only a small increase of self-reported gatekeeper behavior, in line with results from other gatekeeper trainings. Conclusion: The SUPRA gatekeeper training had some beneficial effects in the short- and longterm, with effect sizes comparable to established gatekeeper trainings.